Mushroom residue application affects CH4 and N2O emissions from fields under rice–wheat rotation. Issue 6 (12th May 2017) - Gao, Xuesong; Lan, Ting; Deng, Liangji; Zeng, Min
ABSTRACT: A field experiment involving rice–wheat rotation was performed to investigate the effect of mushroom residue (MR) in comparison with chemical fertilizer (CF) and crop straw return on methane (CH4 ) and nitrous oxide (N2 O) emissions in 2012–2013. Five treatments in quadruplicate were included in this study: (1) CF only, (2) CFS (straw + CF), (3) MR-1 (50% amount of N in CF was replaced with MR), (4) MR-2 (100% amount of N in CF was replaced with MR) and (5) MR-3 (150% amount of N in CF was replaced with MR). Results showed that the effects of CFS and MR-1 treatments on CH4 and N2 O emissions did not significantly differ. By contrast, CH4 emissions decreased as the amount of applied MR increased. Crop straw and MR stimulated CH4 emissions (from 48.8% to 119%) in rice season in 2012. In 2013, the applied crop straw and MR decreased CH4 emissions (from 21.3% to 37.3%). This contrasting effect might be explained by the difference in soil moisture content between the two seasons. N2 O emission in wheat season could be efficiently decreased (from 25.2% to 29.7%) by applying MR. Our results suggesting that MR could be used as a soil organic amendment under the premise of proper water management.